HUBUNGAN PENGETAHUAN, TINGKAT PENDIDIKAN, SUMBER INFORMASI, DAN POLA ASUH DENGAN PERNIKAHAN DINI PADA WANITA - Septianah, Tri Indah; Solehati, Tetti; Widianti, Efri (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2019)
Early marriage is a problem that becoming world?s attention because of the high incidence rate and it is not resolved yet. Some of the factors that causes early marriage are knowledge, education levels, informations source and parenting style. This study aims to determine the relation between knowledge, education levels, informations source, and parenting style with early marriage so this study can reduce the bad impacts of early marriage. This study use a descriptive correlational method with case control approach. The population in this study is woman who were married on 2018 with ratio sample case with control is 1:1 and use simple random sampling. Data will be analyzed using univariate (descriptive) and bivariate (Chi-square and Spearman) analysis. The results of the study showed that there is a difference between knowledge of the respondents who does early marriage with respondents who does not doing early marriage (p=0,000), that there is a difference between education levels of the respondents who does early marriage with respondents who does not doing early marriage (p=0,000), that there is a difference between informations source of the respondents who does early marriage with respondents who does not doing early marriage (p=0,000), that there is a difference between parenting style of the respondents who does early marriage with respondents who does not doing early marriage (p=0,000). There is a relation between knowledge, education levels, informations source, and parenting style with early marriage.